MENINGKATKAN SIKAP PERCAYA DIRI SISWA DALAM TEMA 7 KEBERSAMAAN MELALUI MODEL DISCOVERYLEARNING DI KELAS 2 SDN PANDEAN LAMPER 02 - Muhammad Muhyiddin; Aryo Andri Nugroho; Tri Sugiyono (Universitas Negeri Medan, 2021)
Abstract: The background that drives this research is that students' self-confidence is still low, learning is still on the teacher's side. The purpose of this research is to increase students' self-confidence in Theme 7 Togetherness through the Discovery Learning Model in grade 2 SDN Pandean Lamper 02 Academic Year 2020/2021. This type of research is classroom action research (CAR). This research was conducted at SDN Pandean Lamper 02 in class II. The results of the pre-cycle self-confidence were 10.7% in very high category, 21.4% in high category, 35.7% in moderate category, 32.1% in low category. The result of the percentage of self-confidence in Cycle I was 28.6% in very high category, 28.6% in high category, 17.8% in moderate category, 25% in low category. The results of the percentage of self-confidence in Cycle II are 50% very high category, 25% high category, 14.3% medium category, 10.7% low category. The results of the percentage of self-confidence in Cycle III 64.3% in the very high category, 25% in the high category, 10.7% in the medium category. The conclusion is that this classroom action research has succeeded in increasing students' self-confidence.Keywords: Classroom Action Research, Discovery Learning Model, Students' Self-ConfidenceAbstrak: Latar belakang yang mendorong penelitian ini adalah sikap percaya diri siswa masih rendah, pembelajaran masih bersifat pada guru. Tujuan penelitian ini adalah meningkatkan Sikap Percaya Diri Siswa dalam Tema 7 Kebersamaan melalui Model Discovery Learning dikelas 2 SDN Pandean Lamper 02 Tahun Pelajaran 2020/2021. Jenis penelitian ini adalah penelitian tindakan kelas (PTK). Penelitian ini dilakukan di SDN Pandean Lamper 02 pada kelas II. Hasil presentase sikap percaya diri Prasiklus 10,7% kategori sangat tinggi, 21,4% kategori tinggi, 35,7% kategori sedang, 32,1% kategori rendah. Hasil presentase sikap percaya diri Siklus I 28,6% kategori sangat tinggi, 28,6% kategori tinggi, 17,8% kategori sedang, 25% kategori rendah. Hasil presentase sikap percaya diri Siklus II 50% kategori sangat tinggi, 25% kategori tinggi, 14,3% kategori sedang, 10,7% kategori rendah. Hasil presentase sikap percaya diri Siklus III 64,3% kategori sangat tinggi, 25% kategori tinggi, 10,7% kategori sedang. Kesimpulannya bahwa penelitian tindakan kelas ini berhasil meningkatkan sikap percaya diri siswa.Kata kunci: Penelitian Tindakan Kelas, Model Discovery Learning, Sikap Percaya Diri Siswa